Studying the Effect of Zirconia on Some Physical Properties of Porcelain - Abbas Karim Saadon (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
In this study porcelain was prepared by using composition consisting of raw materials with in following fractions , 50% kaolin , 25% feldspar, and 25% silica( SiO2) tested by XRay diffraction (XRD) method .Study the effect additives at different concentration from zirconia (ZrO2) (2,5,10,15,20) Wt% on some physical properties of porcelain, the sample is prepared by the conventional manufacturing method , It is found that some physical properties of porcelain changes considerably with the substituent sample, It was found that the increase of zrconia (ZrO2) additive of all our sample produce. Increasing in dielectric constant and bulk density and decreasing with open porosity and dielectric loss tangent